Pendampingan Olimpade Sains Nasional (OSN) Tingkat Kabupaten/Kota Melalui Pre-test, Tes Formatif, dan Post-test - Pranata, Ogi Danika (Jurnal Riset dan Pengabdian Masyarakat, 2025)
Mentoring activities for the National Science Olympiad (OSN) at the school level should be provided to prepare students effectively. These activities aim to assess students' initial knowledge, the knowledge acquired during the process, and their knowledge after the mentoring. A community-based research method was applied, and the activities were conducted through various stages. The initial stage involves developing cooperation and a community that supports the development of scientific competence and planning activities. The second stage entails the implementation of mentoring through learning. A strategic approach was adopted, which includes systematically elaborating on the material and conducting three stages of testing: pre-test, formative test, and post-test. This approach allows for the determination of initial knowledge based on pre-test results, knowledge acquisition based on formative test results, and knowledge improvement based on post-test results and N-Gain calculations. Exploration through these stages and tests should be considered when determining the next steps to face challenges in the OSN. The final stage was the evaluation, which aims to assess the effectiveness of the mentoring activities that have been carried out. The results of this assessment can serve as a basis for improving mentoring activities in the future.